2019
DOI: 10.26803/ijlter.18.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Is Personal Life Purpose Replacing Shared Worldview as Youths Increasingly Individuate? Implications for Educators

Abstract: This conceptual paper integrates scholarship from psychology, sociology, education, and philosophy to pose and consider important questions regarding how life purpose and worldview relate, especially in turbulent socio-cultural times. This exploration can help educators consider life purpose not as an individual attribute but rather as a practice. Both worldview and life purpose can be given from a culture or can be chosen by the individual, with more cultures increasingly incorporating individualized choice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…A large-scale, multimethod study of 783 seventh graders in Scotland found a strong, reciprocal connection between life purpose and intentional self-regulation (Linver et al, 2018). Life purpose may be particularly self-regulating in how youth appropriate culturally valued goals, imbue those goals with personal meaning (Kawai & Moran, 2017;Moran, 2014b), align their behavior with those goals even in turbulent or ambiguous situations (Moran, 2017(Moran, , 2019aOyserman & James, 2009), and anticipate the impacts of their behavior over time (Lewis & Oyserman, 2015), including beyond their own lifespans (Moran & Gardner, 2018). Life purpose processes information regarding future self-concept to self-regulate behavior in the present (Moran, 2017).…”
Section: Life Purpose As a Potential In Intrapersonal Intelligencementioning
confidence: 99%
See 4 more Smart Citations
“…A large-scale, multimethod study of 783 seventh graders in Scotland found a strong, reciprocal connection between life purpose and intentional self-regulation (Linver et al, 2018). Life purpose may be particularly self-regulating in how youth appropriate culturally valued goals, imbue those goals with personal meaning (Kawai & Moran, 2017;Moran, 2014b), align their behavior with those goals even in turbulent or ambiguous situations (Moran, 2017(Moran, , 2019aOyserman & James, 2009), and anticipate the impacts of their behavior over time (Lewis & Oyserman, 2015), including beyond their own lifespans (Moran & Gardner, 2018). Life purpose processes information regarding future self-concept to self-regulate behavior in the present (Moran, 2017).…”
Section: Life Purpose As a Potential In Intrapersonal Intelligencementioning
confidence: 99%
“…Thus, life purpose could be viewed as a talented (Gagné, 2004) or excellent (Dai, 2010) form of life goal that stretches individuals' future orientation beyond satisfying their own needs toward making one's mark on the world (Moran, 2017). Whereas generic life goals aim to achieve a desired end to benefit oneself, life purpose recognizes and celebrates how one matters to something greater (Moran, 2009a(Moran, , 2019a. Life purpose focuses on the connection between individual potential and community needs and benefits (Moran, 2018;Tirri & Nokelainen, 2007).…”
Section: Life Purpose As a Potential To Orient Other Talents Toward Pmentioning
confidence: 99%
See 3 more Smart Citations